Fenomena Maraknya Rasa Ketergantungan Peserta Didik Terhadap Kecerdasan Buatan - KURNIAWATI, NUR INDAH (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2023)
Technology that is very developed at this time affects many aspects of life, including in the field of education. One of the rapidly developing technologies is artificial intelligence, which is inseparable from the teaching and learning process. There are various impacts arising from this very rapid technological development, namely the convenience obtained by humans from the existence of artificial intelligence. The researcher took the topic of the problem of whether students' dependence on artificial intelligence can make it difficult for students to solve their own problems. The topic was studied because the researcher wanted to find out whether students' dependence on artificial intelligence could affect students' decision making. The research method used in this study is a qualitative approach by collecting data through literature study. This article shows that the higher the sense of dependence on artificial intelligence, the more it makes learners lose confidence in their ability to solve problems. This thesis statement is the same as the opinion of Gumgum gumelar, Aji Cokro Dewanto, Pyndho Cevin Taraya, Aji Prasetya Wibawa and different from the opinion of Danny Manongga et al, Paulus Wisnu Yudoprakoso, Bambang Karyadi.